Targeted killings law and morality in an asymmetrical world - Finkelstein, Claire Oakes; Ohlin, Jens David; Altman, Andrew, 1950- (Oxford : Oxford University Press, 2012)
The controversy surrounding targeted killings represents a crisis of conscience for policymakers, lawyers and philosophers grappling with the moral and legal limits of the war on terror. This text examines the legal and philosophical issues raised by government efforts to target suspected terrorists.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Targeted killing -- Moral and ethical aspects; War on Terrorism, 2001-2009 -- Moral and ethical aspects; War -- Moral and ethical aspects